Feedlot performance of Angus and Brahman x Angus steers during cold weather - S. Boyles; Jack G. Riley; Ronald V. Pope (Kansas Agricultural Experiment Station Research Reports, 1984)
Straightbred Angus steers gained .21 lb/day faster than Brahman x Angus steers during a 184-day winter feeding trial. Angus steers had a higher yield grade. more fat thickness at 12th rib, and graded 90% Choice. Brahman x Angus steers were 40 days younger at slaughter, had more carcass weight/day of age and larger loin eyes, but only graded 10% choice. There was no difference in feed efficiency.
Keywords: Cattlemen' s Day; 1984; Kansas Agricultural Experiment Station contribution; no. 84-300-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 448; Beef; Feedlot performance; Carcass weight; Yield grade